Patient-reported oral health status and perceptions on oral hygiene before and after oral prophylaxis: A pre-experimental clinical study in Lagos, Nigeria - Afolabi Oyapero; Abiola Adetokunbo Adeniyi; Oluwaseun Fasoyiro; Aliru Idowu Akinleye (Indian Journal of Dental Sciences, 2019)
Background: Constant elimination of bacterial plaque from all nonshedding oral surfaces prevents the progression of periodontal diseases while oral prophylaxis supplements the patient's homecare plaque control. This study compared patient-reported outcomes of oral prophylaxis before and after the procedure and examined the relationship between self-rated and normatively assessed oral health at Lagos State University Teaching Hospital. Methodology: A pre-experimental design was employed while data were obtained using an interviewer-administered questionnaire. Oral cleanliness was documented using a five-point scale while participants' subjective assessment of their oral health status was done on Likert scale. The normative assessment was made with the oral hygiene index-simplified (OHI-S) and the gingival index (GI). Data entry and analysis were performed using the SPSS software version 20, whereas bivariate comparisons were made using the Chi-square and ANOVA tests. A 5% level of statistical significance was adopted. Results: Ninety-two respondents were enlisted. Sixty-seven (72.8%) respondents who rated their oral health as good had better oral hygiene with mean GI of 0.87 and OHI-S of 1.76 compared to the respondents with a poor self-rated oral health who had mean scores of 0.90 and 2.01, respectively. Females 39 (81.2%) had significantly better self-rated oral health (P = 0.048). Poor self-rated oral health was higher among participants with xerostomia and those that infrequently visited the dental clinic; and significantly higher among respondents with difficulty in mastication due to toothache within the past 6 months (6 [75.0%];P= 0.026). Conclusion: There was a positive association between self-rated oral health and normatively assessed oral health status. There was also a significant improvement in the subjects' perception on the benefit of scaling and polishing. The findings highlight the potential role of patients' beliefs and perceptions as potential impetus for treatment provision.